Design, Synthesis, Molecular Docking Studies and Antimicrobial Profiling of 7-Nitroquinazoline Derivatives against Staphylococcus aureus (MRSA) - Halappanavar, Vishwanath; Teli, Sangappa; Teli, Dharyappa; Melavanki, Sammed P. (Asian Journal of Chemistry, 2024)
The alarming increase in antibiotic resistance contributes to the growing risk posed by Staphylococcus aureus (MRSA) in the worldwide healthcare sector. To address the challenge, this study designed, synthesized and evaluated novel quinazoline derivatives, specifically 7-nitroquinazolines, for their antimicrobial efficacy against Staphylococcus aureus (MRSA). Molecular docking studies revealed that compounds 8a and 8b exhibited superior binding affinity to the protein 1T2W, with binding energies of -9.6 kcal/mol and -8.8 kcal/mol, surpassing ciprofloxacin. The derivatives demonstrated favourable pharmacokinetic properties, including moderate lipophilicity, optimal polarity and good water solubility. Compound 8b shows a potent minimum inhibitory concentration (MIC) of 31.1 µg/mL against S. aureus (MRSA ATCC6538), outperforming ciprofloxacin. These findings indicate that compound 8b and related derivatives hold promise as novel therapeutic agents against MRSA, warranting further research to combat the growing issue of antibiotic resistance.